Entre céu e terra: socio-espacialidade dos Mebengôkré-Xikrin. Terra indígena Trincheira Bacajá (T.I.T.B) (Pará, Brasil) - Tselouiko, Stéphanie Anastasia (Universidade Federal de São Carlos, 2018)
The Mebengôkré-Xikrin of the Trincheira Bacajá Indigenous Land (Pará, Brazil) have recently undergone unprecedented political, economic and ecological transformations. These are caused, among other things, by the establishment of the Belo Monte hydroelectric dam and by the compensation projects that accompany it. Among the impacts, the reduction of the hydric regime of their Bacajá river, resulting in an erosion of thebiodiversity and an infringement of their mobility and autonomy in their relationship to the Others. In this context, this thesis aims to analyse how the Xikrin conceive and practice their territoriality as they assert themselves and reproduce as Mebengôkré, and this, in a historical depth allowed by the literature and the speeches of the Ancients. At the crossroads between social anthropology and anthropology of the environment, this research is a continuation of recent work on socio-spatiality that has begun a revision of the idea of ​​closure attributed to the Jê societies and to the Mebengôkré in particular. The hypothesis is that the conceptions and practices of the space lived by the Xikrin are guided by the relation to the Other: the Kuben (the Whites), the Mẽkarõ (the dead) and the animals and plants populating the extra and intra villagers. The thesis is structured according to a three-scale analysis, from the widest to the narrowest: from the region between Central Brazil and the Volta Grande do Xingu to the village, passing through the explored places of the Trincheira Bacajá Indigenous Land. The proposed analysis permits to understand how the Xikrin emerged as a collective apart from the other Mebengôkré, by appropriating the space that today constitutes their territory, in their migration and dispersion through the successive splits since their settlement. This thesis finally shows that the Xikrin, originated from a savanna ecosystem, have not only developed a singular relationship with the city but also with the forest and the rivers of a tropical region. Thus, the conclusions put into question the concentric dual representation of the Xikrin socio-spatiality, allowing to consider the extra villagers spaces and their inhabitants not as simply asocial and potentially socializable but, on the contrary, as being socializing, that is to say also having a role in the (re)production of Mebengôkré people and Xikrin sociality, in particular by learning and appropriating elements of these spaces. ABES
Entre ciel et terre: socio-spatialité des Mebengôkré-Xikrin. Terre Indigène Trincheira Bacajá (T.I.T.B) (Pará, Brésil)
Between sky and earth: socio-spatiality of Mebengôkré-Xikrin.Trincheira Bacajá Indigenous Land (T.I.T.B) (Pará, Brazil)
Keywords: Amazônia brasileira; Projeto de desenvolvimento; Territorialidade; Sócio-espacialidade; Dualismo concêntrico; Atividades produtivas; Rituais; Mẽbêngôkré-Xikrin; Amazonie brésilienne; Projets de développement; Territorialité; Socio-spatialité; Dualisme concentrique; Activités productives; Rituels; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA